Pembuatan Asam Asetat Dari Sari Kulit Nenas (Ananas Comosus) Menggunakan Acetobacter Aceti Dengan Variasi Volume Inokulum Dan Waktu Fermentasi - Multi Handriyani; Chairul Chairul; Cory Dian Alfarisi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Acetic acid is an organic chemical compound that is colorless and has a sharp odor. Pineapple skin can be used as a raw material for making acetic acid by utilizing microorganisms. Microorganisms used to process pineapple skin extract into bioethanol are Saccharomyces cerevisiae and the microorganism used to process bioethanol into acetic acid is Acetobacter aceti. The purpose of this study is to convert sugar in pineapple skin juice through the fermentation process to acetic acid and determine the effect of variations inoculum volume and fermentation time on the resulting acetic acid. This research phase consisted of raw material preparation and inoculum making, fermentation and analysis. The variation of bioethanol fermentation time is 1, 3 and 5 days, while the variation of the inoculum used in this study is 10%; 13%; and 16%. Fermentation results are taken after 1, 3, 5, 7 and 9 days. Optimum fermentation results are bioethanol 5% (v / v) or 39.47 g / L and Yield 53.94% and acetic acid concentration 37.79 g / L and Yield 91.80%. This maximum concentration was obtained on the 9th day of acetic acid fermentation in 13% inoculum of Acetobacter aceti with bioethanol substrate with a fermentation time of 5 days. Keywords : Acetic acid, bioethanol, pineapple skin juice, fermentation, conversion